Prognostic impact of mRNA expression levels of HER1-4 (ERBB1-4) in patients with locally advanced rectal cancer - Kripp, Melanie; Merx, Kirsten; Gaiser, Timo; Schwaab, Juliana; Post, Stefan; Wenz, Frederik; Hofheinz, Ralf-Dieter; Erben, Philipp (Gastroenterology research and practice, 2016)
Background. No predictive or prognostic biomarker is available for patients with locally advanced rectal cancer (LARC) undergoing perioperative chemoradiotherapy (CRT). Members of the human epidermal growth factor receptor (HER) family of receptor tyrosine kinases EGFR (HER1, ERBB1), HER2 (ERBB2), HER3 (ERBB3), and HER4 (ERBB4) are therapeutic targets in several cancers. The analysis was performed to assess expression levels and study the potential prognostic impact for disease-free and overall survival in patients with LARC. Patients and Methods. ERBB1-4 mRNA expression and tumor proliferation using Ki-67 (MKI67) mRNA were evaluated using RT-quantitative PCR in paraffin-embedded tumor samples from 86 patients (median age: 63) treated with capecitabine or 5-fluorouracil-based CRT within a phase 3 clinical trial. Results. A positive correlation of HER4 and HER2, HER3 and HER2, and HER4 and HER3 with each other was observed. Patients with high mRNA expression of ERBB1 (EGFR, HER1) had significantly increased risk for recurrence and death. Patients with high mRNA expression of MKI67 had reduced risk for relapse. Conclusion. This analysis suggests a prognostic impact of both ERBB1 and MKi67 mRNA expression in LARC patients treated with capecitabine or fluorouracil-based chemoradiotherapy.
Gesehen am 12.02.2019